Partitioning of environmental variation in field progeny testing data - GODBOLE, A D; CHAUHAN, V P S; SAIGLA, A K; GUNJAL, M; GUJARATHI, C R (The Indian Journal of Animal Sciences, 2013)
Analyses were conducted to quantify the variation in milk yield due to environmental effects, to decide a suitable model for evaluation of sires in the field progeny-testing scheme of the Department of Animal Husbandry of Maharashtra State. The data consisted of 1 026 first lactation milk yield records of crossbred daughters of 32 Jersey bulls over a period from 1984 to 1990. Analysis was conducted using a model witheffects of zone. district within zone, AI centre within district, year and month of calving and breed group of daughter all filled as fixed effects, and age at first calving as a covariable. Effects of zone, month of calving, sire and age atfirstcalving were insignificant, but the effects of district, AI centre, year of calving and breed group of daughters were significant. The model explained 43% of the total variation in milk yield. The zone effect accounted for negligible amount of variation (0.41 %). However, the district within zone effect accounted for 7.53% and the AI centre within district effect accounted for 15.45% of the total variation. Effect of the breed group of daughter accounted for only 3.0B% of the total variation. It was concluded that a model with cross-classified effect of AI centre (with all othereffecls as filled) would be most appropriate for analysis of milk production data in this progeny testing scheme.